Technology Role in Improving Autodidactic Learning Outcomes at English Language Education - Azmi, Nurul; Daulay, Sholihatul Hamidah (Universitas Jambi, Magister Program of English Education Department, 2024)
This article focuses on the influence of technology on autodidact learning outcomes obtained in the field as a source of data information in our research. We get information from various sources such as google scholar, elicit, and various websites. Furthermore, we tried to review our findings at school with the findings of previous studies to be able to formulate the results of our study. Technology has an important influence on students' interest in learning at school. The results show that the use of technology has an influence in improving students' English language skills by learning autodidactically. Students are expected to be able to utilise technology to support the quality of education at school by learning English autodidactically. The results of this study are expected to be useful for related parties and further research.